(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
In this article, the results of study of androecium and all stages of male generative structures development in Lamium glaberrimum are given. The anthecological morphology of androecium is elucidated. The critical periods of male gametophyte development are revealed.